0919 Health Disparities in the Persistence of Childhood Insomnia Symptoms in the Transition to Adolescence: The Penn State Child Cohort. (27th May 2020) - Bourchtein, E; Puzino, K; Calhoun, S L; Criley, C; He, F; Vgontzas, A N; Liao, D; Bixler, E O; Fernandez-Mendoza, J
Abstract: Introduction: A strong body of cross-sectional evidence indicates that social determinants of health (SDH), such as race, ethnicity, socioeconomic status, and sex/gender, are linked to sleep problems, including insomnia symptoms. Few studies have examined the longitudinal association between SDH and the persistence and remission of insomnia symptoms in the transition between childhood and adolescence, a critical period for sleep health. Methods: The Penn State Child Cohort is a random, population-based sample of 700 children (5-12y at baseline), of whom 421 were followed up as adolescents (12-23y at follow-up). All subjects underwent polysomnography, clinical history, physical exam, and parent- and self-reported scales at baseline and follow-up. Childhood insomnia symptoms were defined as a parent- and/or self-report of difficulty falling and/or staying asleep. All subjects or their parents identified the subject's sex, race, and ethnicity, and reported on socioeconomic status (SES) of the household. Results: Females (32.7%) and racial/ethnic minorities (25.0%) were associated with a significantly lower remission rate as compared to males (53.3%) and non-Hispanic whites (48.3%), respectively. Non-Hispanic whites of low SES were associated with a significantly lower full remission rate (26.3%) as compared to non-Hispanic whites of higher SES (42.0%), while racial/ethnic minorities were associated with the lowest full remission rates regardless of whether they were of low (9.1%) or higher (11.1%) SES. Conclusion: Our novel data indicate that gender-, racial/ethnic- and socioeconomic-related disparities in insomnia not only occur as early as childhood but are important determinants of insomnia's chronic course throughout development. Support: National Institutes of Health (R01HL136587, R01HL97165, R01HL63772, UL1TR000127)